2020
DOI: 10.1016/j.neures.2019.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic modulation of feeding behavior in Caenorhabditis elegans and other related nematodes

Abstract: Serotonin is a conserved neuromodulator that controls feeding behavior in response to environmental inputs in a wide range of species, including the nematode, Caenorhabditis elegans. To understand the detailed mechanism and evolution of serotonergic neuromodulation, the feeding behaviors of C. elegans and related species have been studied intensively because of their simple neural anatomy and genetic manipulability. C. elegans shows patterned movements of a feeding structure called the pharynx, and serotonin m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 94 publications
(167 reference statements)
0
17
0
Order By: Relevance
“…To address this question we decided to look at two sets of muscles; the egg-laying posterior muscles and the pharyngeal muscles. The egg-laying muscles are regulated by multiple neurotransmitters including dopamine [47], while pharyngeal pumping is regulated by serotonin (reviewed in [48]). However, studies have shown that serotonergic behaviors could be modulated by dopamine (reviewed in [49]).…”
Section: Ethanol Exposure Affects Movement In Dop-2 Mutantsmentioning
confidence: 99%
“…To address this question we decided to look at two sets of muscles; the egg-laying posterior muscles and the pharyngeal muscles. The egg-laying muscles are regulated by multiple neurotransmitters including dopamine [47], while pharyngeal pumping is regulated by serotonin (reviewed in [48]). However, studies have shown that serotonergic behaviors could be modulated by dopamine (reviewed in [49]).…”
Section: Ethanol Exposure Affects Movement In Dop-2 Mutantsmentioning
confidence: 99%
“…For instance, in Drosophila adults, activating all 5-HT neurons suppresses food intake whereas activating a smaller yet diverse subset promotes food intake, suggesting heterogeneity in 5-HT regulation of feeding (Albin et al, 2015;Pooryasin and Fiala, 2015). With the exception of a few cases where specific 5-HT neurons that influence feeding have been identified -for example, the 5-HT neurons that promote pharyngeal pumping rate to enhance food ingestion in C. elegans and Drosophila larvae (Ishita et al, 2020;Schoofs et al, 2018;Tierney, 2020) -the diversity of 5-HT neurons that contributes to feeding regulation and their influence on nutrient stores remains largely uncharacterized.…”
Section: -Ht Has Multifaceted Roles In Feeding Regulation and Nutrient Homeostasismentioning
confidence: 99%
“…We first considered the three classic neurotransmitters ACh, Glu and serotonin which are employed in C. elegans much like in the enteric nervous system of other species: Seven of the 14 pharyngeal neuron classes use acetylcholine as neurotransmitter, four use glutamate and one uses serotonin (NSM) (Horvitz et al, 1982;Pereira et al, 2015;Taylor et al, 2021). Of those neurotransmitters, serotonin is perhaps the best studied neurotransmitter both in the vertebrate enteric nervous system (Gershon, 2013) as well as in the nematode pharyngeal nervous system (Horvitz et al, 1982;Ishita et al, 2020;Song and Avery, 2013).…”
Section: Ceh-34 Controls the Expression Of Diverse Neurotransmitter Signaling Pathways In Pharyngeal Neuronsmentioning
confidence: 99%